Human-Animal Interaction Research in School Settings: Current Knowledge and Future Directions - Nancy R. Gee; James A. Griffin; Peggy McCardle (SAGE Publishing, 2017)
The involvement of animals is almost commonplace in many schools, although actual data documenting the extent and nature of human-animal interaction (HAI) in these settings are sparse. We provide an overview of the existing research and argue that the inclusion of animals in classroom settings can have an indirect effect on learning by directly affecting motivation, engagement, self-regulation, and human social interaction through those activities in which the interaction with animals is embedded. We support this theory with examples from the growing body of work indicating that, under specific conditions, with proper safeguards, HAI activities can benefit both typically developing children and those with developmental disabilities by reducing stress and anxiety and improving social interactions and by enhancing motivation, engagement, and learning. Nonetheless, a more comprehensive evidence base is needed to support this theory and to inform policies and practices for HAI in education settings, activities, and interventions.